Hitting the TARGET? A Case Study of the Experiences of Teachers in Steel Mill Learning Centers - Amy D. Rose; Laurel Jeris; Robert Smith (Adult Education Research Conference, 2002)
This paper begins an analysis of the development of professional identity among teachers and coordinators in steel mill learning programs. Teachers and coordinators all have an extreme flexibility in thinking about their own careers and in dealing with the issues that arise in the workplace. They have worked to develop a sense of vision and a philosophy of adult education that allows them to connect with the learners while working at some semblance of professional growth.